Congenital uronephropathy pattern in children - Husein Alatas; Natalina Soesilawati; Bambang Madiyono (Paediatrica Indonesiana, 2001)
To obtain the basic data of congenital uronephropathy pattern and the affecting factors in children, we conducted a cross-sectional study at the Department of Child Health Cipto Mangunkusumo (CM) Hospital Jakarta from 1995 to 1999 and 9 teaching hospitals throughout Indonesia. During the study period 134 patients were obtained, 116 patients from the CM Hospital and 18 patients from other teaching hospitals. Most patients (48.8%) were below 1 year of age; male were affected more than female (2.4:1). The disorder was classified into two groups, i.e., congenital nephropathy and uropathy. There were 10 children with nephropathy, i.e., 4 with unilateral renal hypoplasia, 3 with polycystic kidney, and 3 with renal agenesis. In the uropathy group, 43 were with hypospadia, 22 with primary reflux vesicoureter, 18 with neurogenic bladder, and 17 with ureteropelvic junction obstruction. The complications found were urinary tract infection (71.2%), chronic renal failure (15.7%), hypertension (3.7%), and acute renal failure (1.5%). Consanguinity, familial disorders, maternal diseases, x-ray exposure and abortion efforts were found in a small proportion of patients. History of drug or herbs use in the first trimester of pregnancy was found in a large proportion of patients, mostly took analgesics (especially acetaminophen). In conclusion, uropathy disorders were much more common than congenital nephropathy. The most common complication was urinary tract infection, followed by chronic renal failure, hypertension, and acute renal failure.